Construction and validation of a tool to assess nursing interpersonal relations - Jennifer Specht Dias; Laurelize Pereira Rocha; Deciane Pintanela de Carvalho; Jamila Geri Tomaschewski-Barlem; Edison Luiz Devos Barlem; Graziele de Lima Dalmolin (Revista Brasileira de Enfermagem, 2019)
ABSTRACT Objective: construct and validate a tool to identify the factors that influence interpersonal relations and the health of nursing workers in a University Hospital in the South of Brazil. Method: methodological study, in nine steps. The face validation was carried out, with the participation of five experts, professor nurses doctors in Nursing, content with 26 nurses, stricto sensu Nursing Postgraduate students, and the validation of the construct was performed through a quantitative approach with 213 nursing workers. We used the exploratory factorial analysis and the Cronbach’s Alpha in the validation of the construct. Results: the tool consisted of 29 questions and six constructs were identified. The Cronbach’s Alpha value.879 showed satisfactory internal consistency. Conclusion: the tool was valid and reliable for use in the assessment of interpersonal relations among nursing workers in Brazilian University Hospitals.